Intestinal Atresia: Experience at a Busy Center of North-West India - Shilpi Gupta; Rahul Gupta; Soumyodhriti Ghosh; Arun Kumar Gupta; Arvind Shukla; Vinita Chaturvedi; Praveen Mathur (EL-Med-Pub, 2020)
Objective: To evaluate the presentation, management, complications and outcome of intestinal atresia (IA) managed at our center over a period of 1 year. Materials and methods: Records of patients of IA admitted in our center from January 2015 to December 2015 were retrospectively analyzed. Demographic data, antenatal history, presenting complaints, location (duodenal, jejunoileal, colonic) of atresia, surgery performed and peri-operative complications were noted. Results: Total 78 cases of IA were included in the analyses. Mean age and weight at the time of presentation was 5.8 days (range 0-50), and 1.9 kg (range 1.1-3.2), respectively. IA included duodenal atresia [DA (32)], jejuno-ileal atresia [JIA (40)], colonic atresia [CA (3)] and atresia at multiple-location (sites) in 3 cases. Ninety percent of patients underwent surgery within 5 to 20 hours of admission. All cases of DA except one underwent Kimura's diamond shaped duodeno-duodenostomy. One case with perforated duodenal web underwent duodenotomy with excision of web. Seven patients with JIA and CA required primary stoma, while rest were managed by excision of dilated proximal segment and primary anastomosis. Complications included anastomotic leak in 5, proximal perforation in 2, functional obstruction in 7, aspiration pneumonitis in 3, and wound infection in 6 patients. Mean hospital stay for survivors was 11 days. Overall survival was 63%. Conclusion: Late presentation, overcrowding in intensive care unit, septicemia, functional obstruction and anastomotic leak are the causes of poor outcome in our series. Early diagnosis, some modification in surgical technique, use of total parenteral nutrition and adequate investigations for other congenital anomalies may improve the outcome.